Realities of Female Entrepreneurship in the Cultural Sector: The Case of Cundinamarca, Colombia - Mendivil-Hernández, Patricia María (Journal of Ecohumanism, 2025)
The objective of this study was to identify the realities of female entrepreneurship with an emphasis on the cultural sector in the department of Cundinamarca, Colombia. The methodology adopted was a qualitative approach with a documentary methodological design, analysing secondary sources such as reports, public policies, research and scientific articles. The results showed that, despite public policies aimed at female empowerment and the promotion of cultural entrepreneurship, structural inequalities persist that limit women's participation; female unemployment rates remain high and the gender gap in access to employment opportunities demonstrates the need for more inclusive and specific policies that respond to these realities. In conclusion, while female entrepreneurship, including in the cultural sector, has the potential to act as an engine of regional development in Cundinamarca, its sustainability and expansion require better integration of public policies, focused on reducing gender inequalities and improving access to economic and educational resources.